2006
DOI: 10.1103/physrevb.74.195209
|View full text |Cite
|
Sign up to set email alerts
|

Fractions of singlet and triplet excitons generated in organic light-emitting devices based on a polyphenylenevinylene derivative

Abstract: The effect of magnetic field on the intensity of electroluminescence from devices made of a polyp-phenylenevinylene ͑PPV͒ copolymer was investigated. The emission intensity was enhanced by the application of magnetic field, and the magnitude of the increase depended on operational voltages. When the device was operated under application of low voltages, the intensity increased with magnetic field and reached an 8.5% increase at about 100 mT. With the increase of the operational voltage, the effect of magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 39 publications
4
42
0
Order By: Relevance
“…Further support for this picture of device operation and the key role of TTA in enhancing the electroluminescent yield was given by Iwasaki et al who have made an interesting observation on the role of triplet triplet annihilation [124]. From magnetic field dependencies of the TTA process, they conclude that in fact TTA contributes substantially to the final singlet yield.…”
Section: Historical Perspective On Ttamentioning
confidence: 79%
“…Further support for this picture of device operation and the key role of TTA in enhancing the electroluminescent yield was given by Iwasaki et al who have made an interesting observation on the role of triplet triplet annihilation [124]. From magnetic field dependencies of the TTA process, they conclude that in fact TTA contributes substantially to the final singlet yield.…”
Section: Historical Perspective On Ttamentioning
confidence: 79%
“…We recently observed [4] a large, low field magnetoresistive effect (up to 10% at 10 mT and 300 K) in OLEDs, which we dubbed organic magnetoresistance (OMAR). Other laboratories have also observed this effect [16][17][18][19][20][21]. OMAR poses a significant scientific puzzle since it is, to the best of our knowledge, the only known example of large room temperature magnetoresistance in non-magnetic materials with the exception of very-high-mobility materials [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Using layered devices based on Bphen/MTDATA -a well-known exciplex emitter -we show that the increase in EL emission intensity I due to small applied magnetic fields of order 100 mT is markedly larger at the high-energy blue end of the EL spectrum (∆I/I ∼11%) than at the low-energy red end (∼4%). Concurrently, the widths of the magneto-EL curves increase monotonically from blue to red, revealing an increasing hyperfine coupling between polarons and nuclei and directly providing insight into the energy-dependent spatial extent and localization of polarons.Several recent experiments have shown that small applied magnetic fields B on the order of 10-100 mT can induce substantial (∼10%) changes in the total light intensity emitted by organic light-emitting diodes (OLEDs) [1][2][3][4][5][6][7][8][9][10][11][12][13]. While initially surprising in view of the fact that the polymers and small molecules used in OLEDs are primarily composed of non-magnetic atoms (H, C, N), it was quickly appreciated that hyperfine spin interactions underpinned these phenomena.…”
mentioning
confidence: 99%
“…This precession leads to spin mixing between singlet and triplet polaron-pair states, which are precursors to exciton or exciplex formation in an OLED. Applied fields B suppress this hyperfineinduced mixing, altering the population balance between singlet and triplet excitons or exciplexes, which in turn modifies the electroluminescence (EL) efficiency.The detailed dependence of EL intensity on B allows direct insight into not only the rates of singlet and triplet exciton/exciplex formation, but also reveals the strength of hyperfine coupling and therefore provides a measure of the spatial extent (size) of the electron and hole polarons.In magneto-EL studies to date [1][2][3][4][5][6][7][8][9][10][11][12][13], only the total (spectrally-integrated) EL intensity was measured as a function of B. However, OLED emission spectra typically span a very broad wavelength range, reflecting the fact that excitons and exciplexes form over a wide range of energies, and with varying degrees of localization for which different hyperfine couplings may be expected.…”
mentioning
confidence: 99%
See 1 more Smart Citation